Legal Reform as an Administrative Decision: The Risks and Performance Criteria - SMORGUNOVA, Valentina Yu; DORSKAIA, Аleksandra А.; PASHENTSEV, Dmitriy А.; PAVLENKO, Evgeniya M.; IGNATIEVA, Marina V. (Journal of Advanced Research in Law and Economics, 2017)
The article discusses various approaches to the definition of the concept of legal reform: legal reform is the reform of legislation or legal reform is the change of the sense of justice. It is shown that the decision to start the development and implementation of a legal reform in any country of the world can only be taken by public authorities. The successful as well as the failed reforms are attributed to social upheaval. Risks of legal reforms’ implementation are identified and characterized. The quality of life improvement can be associated with an increase in material well-being, and expressed in greater security, the preventive measures of the state to prevent the commission of crimes, raising the level of legal awareness, the development of law enforcement practice. It is human and civil rights that can serve as the indicator that reveals the true purpose of a specific legal reform. The possible classification of legal reforms and the criteria for their performance are analyzed (stability of certain legal reforms; temporary certainty; improve in the quality of life, if not every member of society, but the majority; parallelism of legal reforms and reforms in the public system; small number of laws; compliance of national legislation with international legal standards; state of legal education).
Keywords: administrative decision; Russia; legal reform; performance criteria of reforms; reforms classification; risks